Aerosol Generation in Ear Canal and Air-Fluid Interface Suction. Issue 3 (July 2021) - Bahgat, Mohammed; Lindsey, Leon; Lindsey, Paul; Knight, Andrew
Objective: The identification of aerosol-generating procedures (AGPs) is important during the current SARS-CoV-2 pandemic due to aerosol-mediated virus transmission. Aerosol measurement during clinical procedures using particle counting may be confounded by variable natural background aerosol levels or limited by partial volume sampling. The study objective was to quantify any significant aerosol generated from simulated suction clearance procedures. Study Design: Prospective quantification of aerosol generation during clinical suction simulation. Setting: Clean chamber. Methods: We created a clean environment for particle counting in a transparent neutralized polypropylene chamber. Air was passed through a HEPA 14 class filter to maintain a constant chamber inlet pressure. An optical particle counter was connected in line to the chamber exhaust vent to measure all of the vented particles. The chamber background count was 1 particle ≥0.3 µm per 15 minutes at a flow rate of 1 chamber air change per minute. We used this system to quantify very low aerosol counts generated from suction clearance of a silicone ear canal and at an open air-fluid interface. Results: No clinically significant aerosol generation was found by particle counting of the whole chamber air volume during simulated suction procedures. Conclusion: Simulated ear suction clearance and air-fluid interface suction does not generate any significant aerosol. It appears likely that any aerosol potentially generated at the suction tube tip is entrained by incoming air flow. This is the first study to quantify aerosols generated by suction in a controlled environment; further research is required to determine its clinical implications.